The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.06.09.142653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chitosan induces plant hormones and defences in tomato root exudates

Abstract: In this work, we use electrophysiological and metabolomic tools to determine the role of chitosan as plant defence elicitor in soil for preventing or manage root pests and diseases sustainably. Root exudates include a wide variety of molecules that plants and root microbiota use to communicate in the rhizosphere. Tomato plants were treated with chitosan. Root exudates from plants were analysed at 3, 10, 20 and 30 days after planting (dap). We found, using High Performance Liquid Chromatography (HPLC) and Excit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Using other organic acids such as citric and ascorbic acids, which are known for their stimulant activities on plants [ 24 ], could lead to synergetic effects, which might increase the performance of the biostimulant. Recently, several researchers demonstrated the stimulating effect of chitosan against abiotic stress on tomato plants [ 25 , 26 , 27 , 28 ]. Moreover, [ 29 ] reported that foliar application of chitosan ameliorates the negative impact of salinity on tomato plants through enhancing growth aspects and photosynthetic pigments.…”
Section: Introductionmentioning
confidence: 99%
“…Using other organic acids such as citric and ascorbic acids, which are known for their stimulant activities on plants [ 24 ], could lead to synergetic effects, which might increase the performance of the biostimulant. Recently, several researchers demonstrated the stimulating effect of chitosan against abiotic stress on tomato plants [ 25 , 26 , 27 , 28 ]. Moreover, [ 29 ] reported that foliar application of chitosan ameliorates the negative impact of salinity on tomato plants through enhancing growth aspects and photosynthetic pigments.…”
Section: Introductionmentioning
confidence: 99%
“…Authors also wish to thank Mr. Arnau Hernández Royo for his help conducting electrophysiological and microscopy experiments. This manuscript has been released as a pre-print at bioRXiv ( Suarez-Fernandez et al, 2020 ).…”
mentioning
confidence: 99%